Impact of COVID-19 on healthcare organisation and cancer outcomes. (August 2021) - Bardet, Aurelie; Fraslin, Alderic M.; Marghadi, Jamila; Borget, Isabelle; Faron, Matthieu; Honoré, Charles; Delaloge, Suzette; Albiges, Laurence; Planchard, David; Ducreux, Michel; Hadoux, Julien; Colomba, Emeline; et al.
Abstract: Background: Changes in the management of patients with cancer and delays in treatment delivery during the COVID-19 pandemic may impact the use of hospital resources and cancer mortality. Patients and methods: Patient flows, patient pathways and use of hospital resources during the pandemic were simulated using a discrete event simulation model and patient-level data from a large French comprehensive cancer centre's discharge database, considering two scenarios of delays: massive return of patients from November 2020 (early-return) or March 2021 (late-return). Expected additional cancer deaths at 5 years and mortality rate were estimated using individual hazard ratios based on literature. Results: The number of patients requiring hospital care during the simulation period was 13, 000. In both scenarios, 6–8% of patients were estimated to present a delay of >2 months. The overall additional cancer deaths at 5 years were estimated at 88 in early-return and 145 in late-return scenario, with increased additional deaths estimated for sarcomas, gynaecological, liver, head and neck, breast cancer and acute leukaemia. This represents a relative additional cancer mortality rate at 5 years of 4.4 and 6.8% for patients expected in year 2020, 0.5 and 1.3% in 2021 and 0.5 and 0.5% in 2022 for each scenario, respectively. Conclusions: Pandemic-related diagnostic and treatment delays in patients with cancer are expected to impact patient survival. In the perspective of recurrent pandemics or alternative events requiring an intensive use of limited hospital resources, patients should be informed not to postpone care, and medical resources for patients with cancer should be sanctuarised. Highlights: Delay of >2 months for cancer treatment is estimated in 6–8% of patients. Additional cancer deaths at 5 years will be observed for 2020 patients. Impact is mainly found on sarcoma, gynaecological, liver, head and neck, breast cancer and acute leukaemia. Patients should be informed not to postpone cancer diagnosis and treatment.